(untitled) (Journal of Artificial Intelligence & Research, 2024)
This paper examines the application of Artificial Intelligence (AI) in optimizing resource allocation within Agile project management environments. Agile methodologies are characterized by their iterative development cycles and a focus on flexibility and responsiveness to change. However, optimizing resource allocation in such dynamic settings can be challenging. This research explores various AI-driven strategies that enhance resource management without compromising the inherent flexibility of Agile practices. By analyzing case studies and current literature, the paper highlights how AI can facilitate more efficient resource utilization, improve decision-making processes, and ultimately lead to better project outcomes. The findings indicate that AI technologies not only support efficiency but also enhance the adaptability of Agile teams, enabling them to respond effectively to evolving project requirements.